Asymptotics for Gegenbauer-Sobolev orthogonal polynomials associated with non-coherent pairs of measures - de Andrade, E. X. L. [UNESP]; Bracciali, Cleonice Fátima [UNESP]; Ranga, Alagacone Sri [UNESP] (IOS Press, 2008)
Inner products of the type < f, g >(S) = < f, g >psi(0) + < f', g'>psi(1), where one of the measures psi(0) or psi(1) is the measure associated with the Gegenbauer polynomials, are usually referred to as Gegenbauer-Sobolev inner products. This paper deals with some asymptotic relations for the orthogonal polynomials with respect to a class of Gegenbauer-Sobolev inner products. The inner products are such that the associated pairs of symmetric measures (psi(0), psi(1)) are not within the concept of symmetrically coherent pairs of measures.
Keywords: Orthogonal polynomials; Sobolev orthogonal polynomials; Asymptotic